Creative Management in Ukraine’s Digital Economy: European Experience and Strategic Development Guidelines - MOSTOVA, A. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article examines the role of creative management as a strategic resource of the digital economy. It defines its conceptual foundations, functions, and connection with the development of human and cultural capital. The European experience of integrating creativity, digital technologies, and sustainable development is analyzed based on the Creative Europe, Digital Europe, and European Green Deal programs. The significance of creative management for Ukraine’s post-war recovery is substantiated, emphasizing the development of creative-digital competences, institutional support, startup ecosystems, and the implementation of artificial intelligence technologies. The article outlines key directions for strengthening creative management’s role in building an innovative, competitive, and sustainable Ukrainian economy.